The Effect of Carrageenan and Glycerol Addition on the Physicochemical Characteristics of Nori, an Analogue of Genjer Leaves (Limnocharis flava) - Sukma Ayu Puspa Simangunsong; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Analogue nori is produced through cooking, molding, and drying processes using non- seaweed materials. This study utilized genjer leaves (Limnocharis flava) as the primary raw material due to their physical resemblance to commercial nori, with carrageenan added as a gelling agent to improve structural compactness and glycerol as a plasticizer to enhance moisture retention and flexibility. The objective was to determine the optimal carrageenan–glycerol proportion to obtain the best physicochemical qualities. A two-factor Completely Randomised Design with two replications was applied, consisting of carrageenan (1%, 1.5%, and 3%) and glycerol (1%, 1.5%, and 2%) concentrations. The optimal treatment (3% carrageenan and 2% glycerol) produced analogue nori with 14.44% moisture, 12.03% ash, 17.22% fat, 5.31% crude fiber, 5.74% dietary fiber, 40.57% antioxidant activity, 0.45 mg/kg lead, and a tensile strength of 0.0148 N/mm², indicating its potential as a functional nori alternative Contribution to Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 12 : Responsible Consumption and ProductionSDG 14 : Life Below Water